Achados oftalmológicos em pacientes com AIDS - Curi, André L.L. (Brazilian Journal of Sexually Transmitted Diseases, 1997)
From february 1996 to april 1997, tlte autlior st udied 300 patients witlt Acquired Immunodeficiency Syndrome (AIDS). Outof tliese pat.ients 197 (65, 7%) weremalemzd 103 (34,3%) female. The parients weredivided in 4 groups: below 20 years old, 20-39, 40-59, above 60 years old. We found oplthalmic changes in 126 ( 42%) patients. The most frequent finding was the HIV retinophathy, (ound in 41 (13, 6%) patients, bilateral in 15 (36,5%). The citomegalovirus retinitis was found in 29 (9,6%), bilateral in 8 (27,5%). Neurophthalmie findings occured in 16 (5,3%) patients. Toxoplasmosis in 3 (1%) , BK choroiditis in 3 (1%) and acute retina necrosis in 3 (1%) patients were other findings. We found 2 (0,6%) cases of syphilitic uveitis, cryptococcal choroidiris, ophthalmic herpes and progressive outer retina necrosis (PORN) .